The MRL model: an invaluable tool in studies of autoimmunity-brain interactions - Sakić, Boris (Methods in molecular biology (Clifton, N.J.), 2012)
The link between systemic autoimmunity, brain pathology, and aberrant behavior is still largely unexplored field of biomedical science. Accumulating evidence points to causal relationships between immune factors, neurodegeneration, and neuropsychiatric manifestations. By documenting autoimmunity-associated neuronal degeneration and cytotoxicity of the cerebrospinal fluid from disease-affected subjects, the murine MRL model had shown high validity in revealing principal pathogenic circuits. In addition, unlike any other autoimmune strain, MRL mice produce antibodies commonly found in patients suffering from lupus and other autoimmune disorders. This review highlights importance of the MRL model as an indispensible preparation in understanding the links between immune system and brain function.